2006
DOI: 10.1016/j.mcn.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the β4 and α5 integrin subunits in cerebral blood vessels of transgenic mice chronically producing the pro-inflammatory cytokines IL-6 or IFN-α in the central nervous system

Abstract: Evidence suggests that vascular function is strongly regulated by extracellular matrix (ECM) proteins via integrin-mediated signaling. To determine whether integrin expression on cerebral blood vessels is altered during chronic neuroinflammation, we examined β1 and β4 integrin expression in transgenic mice with astrocyte production of the pro-inflammatory cytokines interleukin-6 (IL-6) or interferon-α (IFN-α). Chronic production of IL-6 or IFN-α in the CNS promoted vascular expression of the β4 and α5 integrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 58 publications
4
41
0
1
Order By: Relevance
“…The microenvironment of the cerebellum in the GFAP-IL6 mice is characterized by chronic activation of the vascular endothelium. In particular, the levels of the cellular adhesion molecules ICAM-1 and VCAM-1 as well as a number of integrins is increased significantly on vascular endothelium (19,38). This pre-existing activation state of the vascular endothelium in the cerebellum of the GFAP-IL6 mice would be expected to favor the increased adhesion and subsequent transendothelial migration of leukocytes following MOG-immunization.…”
Section: Discussionmentioning
confidence: 97%
“…The microenvironment of the cerebellum in the GFAP-IL6 mice is characterized by chronic activation of the vascular endothelium. In particular, the levels of the cellular adhesion molecules ICAM-1 and VCAM-1 as well as a number of integrins is increased significantly on vascular endothelium (19,38). This pre-existing activation state of the vascular endothelium in the cerebellum of the GFAP-IL6 mice would be expected to favor the increased adhesion and subsequent transendothelial migration of leukocytes following MOG-immunization.…”
Section: Discussionmentioning
confidence: 97%
“…One possibility is that MECA-32 expression reflects altered activation status of brain endothelial cells, akin to induction of VCAM-1 and ICAM-1, and that MECA-32 expression is part of a stress-induced early response common to hypoxia and inflammation. Alternatively, as angiogenesis often accompanies inflammation (Campbell et al, 1993;Milner and Campbell, 2006), induction of the MECA-32 antigen may represent early angiogenic events associated with inflammation.…”
Section: Temporal Expression Pattern Of Fibronectin α5 Integrin and mentioning
confidence: 99%
“…Microglia on an LN substrate adopt a less activated, poorly adhesive phenotype and show reduced levels of expression of the activation markers (32). It has also been shown that microglial adhesion to LN is mediated entirely by the ␣6␤1 integrin, and microglial adhesion to LN was increased significantly by the proinflammatory cytokines (6,33). However, cytokines did not change ␣6␤1 expression levels but altered the activation state of ␣6␤1, mediated by a PKC-dependent mechanism.…”
Section: Discussionmentioning
confidence: 98%